Customer obsessed a whole company approach to delivering exceptional customer experiences - Berridge, Eric (Wiley, 2016)
Leverage the cloud into competitive advantage through optimized customer experience Customer Obsessed looks at customer experience through the lens of the cloud to bring you a cutting-edge handbook for customer experience. Cloud technology has been hailed as a game-changer, but a recent IDC report shows that it accounts for less than three percent of total IT spending; why are so many companies neglecting such an enormous asset' This book provides a high-level overview of how the cloud can give you a competitive advantage. You'll learn how to integrate cloud technology into sound customer experience strategy to achieve unprecedented levels of success. More than just a state-of-the-field assessment, this book offers a set of concrete actions you can take today to leverage cloud computing into technical innovation and better business outcomes at all levels of your organization. You'll examine the many factors that influence the customer experience, and emerge with the insight to fine-tune your approach using the power of the cloud. What kind of advantage is your company leaving on the table' This book guides you through the key drivers of customer success to help you optimize your approach and leverage the future of global technology.-Learn the keys to competitive advantage in the digital era -Gain insight into each element that affects customer experience -Harness the power of the cloud to achieve customer success -Follow a prescriptive framework for optimizing customer experience We are in the golden age of IT innovation, but the majority of companies haven't even adopted cloud technology, much less begun to utilize its full business capabilities. Jump into the gap now, and reap the benefits as other struggle to catch up. Customer Obsessed gives you the guidance you need to achieve sustainable success in today's digital world.
Includes bibliographical references and index. - Online resource; title from PDF title page (EBSCO, viewed October 5, 2016)
Keywords: Selling -- Computer programs; Organizational change; Consumer behavior; Cloud computing; Logiciels; Vente; Changement organisationnel; Consommateurs; Comportement; Infonuagique; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Selling; Computer programs